Brazilian Canephora coffee evaluation using NIR spectroscopy and discriminant chemometric techniques. - BAQUETA, M. R. (2023)
High-quality Brazilian Canephora coffees are rising to the level of specialty coffees in the face of a new industry perception. In this framework, spectra from 527 coffees were analyzed in the near-infrared (NIR) region. Prin- cipal component analysis distinguished Brazilian Canephora producing states, botanical varieties, low and high- quality Canephora, Canephora and Arabica, and Canephora with geographical indication (GI) from those without GI. Also, Canephora coffee cultivars from Western Brazilian Amazon were distinguished. Three multi-class PLS- DA (traditional, hard, and soft versions) were compared to discriminate 5 classes: Robusta Amaz?onico from traditional (1) and indigenous (2) producers of Rond?onia, Conilon from Espírito Santo (3), Conilon from Bahia (4), and specialty Arabica (5). Binary PLS-DA discriminated GI Canephora and non-GI Canephora with 100% sensitivity and specificity. Carbohydrates, chlorogenic acids, lipids, caffeine, and proteins were dominant ab- sorption bands in coffee classifications. The proposed method is objective, simple, fast, and could be used in the routine analysis of coffee to verify claims of identity, variety, and origin.